Obstetric Nurses Perceptions About Work-Related Musculoskeletal Disorders: Photovoice Study - Armando David de Sousa; Cristina Lavareda Baixinho; Maria Helena Presado; Maria Adriana Henriques (Global Qualitative Nursing Research)
Obstetric nurses are at increased risk of work-related musculoskeletal disorders associated with equipment and materials, the parturient and the specific nature of their work. We used the photovoice method to identify obstetric nurses’ perceptions of work-related musculoskeletal injuries involving 20 participants who worked in the delivery room. A total of 100 photographs were captured by participants and their narratives were obtained through 20 interviews. Analysis of the photographs, the nurses’ descriptions of the photos, the researcher’s field notes and the interviews, resulted in three semantic categories: perception of risk, perception of preventive measures and musculoskeletal symptoms, and one expressive category related to decision-making. Perceived risks for musculoskeletal injury were associated with workspaces, the precariousness of the equipment and materials, and the organization and nature of obstetrical nurses’ work. The importance of preventive measures was recognized and reinforced by reports of transitory work-related musculoskeletal symptoms by 18 of 20 obstetric nurses participating in the study. The strategies perceived by the obstetric nurses as potentially effective for preventing musculoskeletal injury included improvements to the physical work environment and equipment, sensitization of the team to the problem, and developing biomechanical skills in situ through simulated exercises and peer support